2018
DOI: 10.1038/s41467-017-02696-6
|View full text |Cite
|
Sign up to set email alerts
|

Bifunctional immune checkpoint-targeted antibody-ligand traps that simultaneously disable TGFβ enhance the efficacy of cancer immunotherapy

Abstract: A majority of cancers fail to respond to immunotherapy with antibodies targeting immune checkpoints, such as cytotoxic T-lymphocyte antigen-4 (CTLA-4) or programmed death-1 (PD-1)/PD-1 ligand (PD-L1). Cancers frequently express transforming growth factor-β (TGFβ), which drives immune dysfunction in the tumor microenvironment by inducing regulatory T cells (Tregs) and inhibiting CD8+ and TH1 cells. To address this therapeutic challenge, we invent bifunctional antibody–ligand traps (Y-traps) comprising an antibo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

11
196
0
3

Year Published

2018
2018
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 260 publications
(223 citation statements)
references
References 72 publications
11
196
0
3
Order By: Relevance
“…Consistent with these findings, previous studies involving preclinical models of advanced cancer with activation of TGFb-and EMT-relevant pathways, as well as fibroblast proliferation, demonstrated the inhibition of T cell-mediated tumor killing and a decrease in T-cell trafficking into tumors (13,61). In line with our findings, some preclinical studies have indicated that antibody-ligand traps (anti-CTLA4-TGFbRII and anti-PDL1-TGFbRII) exhibit a superior therapeutic index compared with those of their parent immune-checkpoint inhibitors, which are currently in clinical use (73,76).…”
Section: Discussionsupporting
confidence: 88%
“…Consistent with these findings, previous studies involving preclinical models of advanced cancer with activation of TGFb-and EMT-relevant pathways, as well as fibroblast proliferation, demonstrated the inhibition of T cell-mediated tumor killing and a decrease in T-cell trafficking into tumors (13,61). In line with our findings, some preclinical studies have indicated that antibody-ligand traps (anti-CTLA4-TGFbRII and anti-PDL1-TGFbRII) exhibit a superior therapeutic index compared with those of their parent immune-checkpoint inhibitors, which are currently in clinical use (73,76).…”
Section: Discussionsupporting
confidence: 88%
“…These observations imply that additional immunosuppressive mechanisms such as those mediated by PD-1 whose expression was unaffected in tumor-infiltrating CD8 + T cells (Fig. 1b), may compensate for TGFβ signaling blockade for CTL repression as suggested by recent studies 20-23 .…”
Section: Textsupporting
confidence: 57%
“…Ongoing trials of the TGF‐β antibody galunisertib plus nivolumab and durvalumab are being explored in pancreatic cancer, NSCLC, hepatocellular carcinoma, and other solid tumors. Additionally, an extremely promising strategy to target TGF‐β involves using a bispecific antibody against PD‐L1 or CTLA‐4 with a TGF‐β trap . Dramatic responses were observed with this drug in cervical cancers and pancreatic cancers, with an ongoing study including multiple expansion cohorts .…”
Section: Sarcomas—a Framework For Approaching Modern Immunotherapymentioning
confidence: 99%